Resistência e luta pela terra no território Cantuquiriguaçu-Paraná - Moraes, Vitor de (2021)
In this assignment were investigated and analyzed elements of farmer re-creation, historically inherent to the resistance and to the fight for the land, having as cutout the territory of Cantuquiriguaçu – PARANA – BRAZIL (TC1). Evince the Farmer Territory (TC2), the elements of re-creation existent in culture, in life production, in fight and resistance, in relation to the familiar work, community, in relation to the land, as well as contradictions current through the conflicts, the disputes and the tackling in agribusiness advance about the TC2. It was considered, hypothetically, that there is in TC1 the farmer re-creation through the resistance and the fight for the land enduring to the manner of capitalist production, in constant conflict, in continuity and discontinuity. In this respect, the tools of study presented and analyzed in this assignment introduce the territories and the countryside landscapes and of the agribusiness. The analyzes were developed through the dialectical and historic materialism, being the methodology based on quantitative, qualitative and collaborative from field research, bibliographic research, documental research and comparisons. The technical contribution of this assignment presents the Agriculture Issue Paradigm (AIP) against the Paradigm of Agrarian Capitalism (PAC) in defense of farmer re-creation. This research is of extreme importance, because, besides to evidence the dispute among the farmers and the agribusiness, evidence the reality of Cantuquiriguaçu Territory, presenting two sceneries: homogeneous scenery of agribusiness, land based, monocultures, toxic agronomic substance and big farming equipment, and the peasantry heterogeneous scenery, based in the land of work, production of life, which reality has been built by leadership of Popular Social Movements in the Countryside (PSMC) and also by farmer non organized in movement. We can conclude that the Cantuquiriguaçu Territory configures itself, in practice of peasantry, with a territory of conflicts, of disputes, with fights, resistance and tackling to the agribusiness while they break the fences of land property and produce other kind of scenery and territory, with the polyculture and keep the essence of familiar work, of relation to the land and the production of life with specific cultural and social ties. The peasantry adopt relation with the State in sense of intend their demands in relation to production and marketing as strategies of resistance and re-creation. Nevertheless, the fight and resistance for land and rights are crucial factors to the creation, re-creation and the maintenance of peasantry, even with the advance of agribusiness. The peasantry in TC1 indicates to the possibility of human and political emancipation, presents the agroecology as potentiality and, concurrently, the utopia of a society lined in equity, in democracy and solidarity.